2017
DOI: 10.7567/jjap.56.08mc09
|View full text |Cite
|
Sign up to set email alerts
|

Conduction band offset engineering in wide-bandgap Ag(In,Ga)Se2solar cells by hybrid buffer layer

Abstract: Ag(In,Ga)Se 2 (AIGS) is one of the promising candidates for the top cell absorber in the tandem structure. However, the conversion efficiency of AIGS solar cells is still lower than that required for the top cell. In this study, to improve the conversion efficiency of AIGS solar cells, we controlled the conduction band offset (CBO) at the buffer layer/ZnO and buffer layer/AIGS interfaces. The reduction in interface recombination at the CdS buffer layer/AIGS interface was achieved by introducing a ZnS(O,OH) buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Later, in 2009, an efficiency of 13.0% ( V OC = 890 mV) was achieved by using an ACIGS absorber with E g = 1.60 eV ([Ag]/([Ag] + [Cu]) ≡ Ag/I = 0.75 and GGI = 0.8) . Recently, in 2017, an efficiency of 9.4% and V OC = 960 V was reached for AIGS with E g = 1.75 eV by using a ZnS(O,OH)/CdS hybrid buffer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in 2009, an efficiency of 13.0% ( V OC = 890 mV) was achieved by using an ACIGS absorber with E g = 1.60 eV ([Ag]/([Ag] + [Cu]) ≡ Ag/I = 0.75 and GGI = 0.8) . Recently, in 2017, an efficiency of 9.4% and V OC = 960 V was reached for AIGS with E g = 1.75 eV by using a ZnS(O,OH)/CdS hybrid buffer …”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, in 2017, an efficiency of 9.4% and V OC = 960 V was reached for AIGS with E g = 1.75 eV by using a ZnS(O,OH)/CdS hybrid buffer. 25 Several changes in material properties are reported when adding…”
mentioning
confidence: 99%
“…[24] Consequently, some promising V OC values (890-960 mV) could be achieved for ACIGS solar cells with E g ¼ 1.60-1.75 eV and [Ag]/([Ag]þ[Cu]) (AAC) ratios ≥ 0.75. [25][26][27][28] In previous studies, a substantial formation of OVCs was found for group-I (I)-deficient ACIGS within the compositional window of GGI > 0.5 and AAC > 0.5. [29,30] Further investigations revealed that these OVCs are present in the form of isolated patches located at the interfaces, as a consequence of the applied three-stage deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Several promising results, with V OC values of 890 mV ≤ V OC ≤ 960 mV and efficiencies of 13% ≥ η ≥ 9.3%, were reported for A(C)IGS solar cells with 1.6 eV ≤ E G ≤ 1.75 eV. [ 20–22 ] However, these efficiencies are still too low to consider wide‐gap ACIGS as a practical top cell absorber material.…”
Section: Introductionmentioning
confidence: 99%